TAHAPAN UNDANG-UNDANG RESPONSIF - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Law-making in Indonesia is generally based on formal-legal aspects and legislators political will, thus resulting in legislations that do not conform to societys aspirations nor answer their needs. This paper discusses a responsive model legislation hence it could meet community needs, provide legal certainty, and ensure justice and welfare.